Changing food webs before and during the Last Glacial Maximum based on stable isotopes of animal bone collagen from Lower Austria - Reiss, Lilian; Mayr, Christoph; Pasda, Kerstin; Einwögerer, Thomas; Händel, Marc; Lücke, Andreas; Maier, Andreas; Wissel, Holger (Journal of Quaternary Science, 2023)
We investigated palaeofood web structures using stable isotope analyses on animal bone collagen from four Upper Palaeolithic sites dated to the Early Gravettian (Krems-Hundssteig and Krems-Wachtberg: 33–31k cal a bp, Langenlois: 31–29k cal a bp) and to the Early Epigravettian (Kammern-Grubgraben: 24–20k cal a bp). In both periods, δ13C values show niche partitioning between hare, horse and mammoth on one side, and reindeer and ibex on the other, indicating different diets and habitats between both herbivore groups. The δ15N differences between carnivores and herbivores suggest a difference of one trophic level during the pre-Last Glacial Maximum (pre-LGM) period at the Early Gravettian sites and a tendency towards secondary carnivores during the LGM at Kammern-Grubgraben. δ15N values of pre-LGM mammoths are elevated in relation to other herbivores but shifted to the level of other herbivores in the LGM. A general δ15N value shift in herbivores of 3.3‰ from the pre-LGM to the LGM is related to climatic deterioration. This may have led to the disappearance of certain ecological niches and to a shift from broader to overlapping ecological herbivore niches shortly before the LGM, as demonstrated by SIBER analyses.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Epigravettian; Gravettian; niche partitioning; δ; δ

Evaluation of geochemical proxies and radiocarbon data from a loess record of the Upper Palaeolithic site Kammern-Grubgraben, Lower Austria - Reiss, Lilian; Stüwe, Christian; Einwogerer, Thomas; Handel, Marc; Maier, Andreas; Meng, Stefan; Pasda, Kerstin; Simon, Ulrich; Zolitschka, Bernd; Mayr, Christoph (E&G : Quaternary Science Journal, 2022)
Two loess sections from the Upper Palaeolithic site of Kammern-Grubgraben (Lower Austria) were analysed to test geochemical proxies, as well as radiocarbon data of different components, for their reliability and consistency in an archaeological context. Only a reliable basal age (28.9-27.8 ka cal BP) was obtained from charcoal fragments derived from a tundra gley underlying the archaeological horizons and assigned to Greenland Interstadials 3 or 4. Grain size, organic and inorganic geochemistry, and stable isotopes of the fine organic fraction (delta C-13(org)) and of rhizoconcretions (delta C-13, delta O-18) were analysed to provide information on palaeoenvironmental conditions. Low-resolution geochemical and sedimentological analyses document a humidity-related variability, while delta C-13(org) values indicate predominant C-3 vegetation. High-resolution elemental variations derived from X-ray fluorescence scanning exhibit increasing Ca and decreasing Fe and Ti values, indicating drier conditions towards the top. Secondary pedogenic carbonate concretions provide post-sedimentary (Holocene) ages and are not suitable for assessing climate and environmental changes for the Palaeolithic.
CRIS-Team WoS Importer:2022-03-18

Seasonal climate variations during Marine Isotope Stages 3 and 2 inferred from high-resolution oxygen isotope ratios in horse tooth enamel from Lower Austria - Reiss, Lilian; Mayr, Christoph; Pasda, Kerstin; Joachimski, Michael; Einwögerer, Thomas; Händel, Marc; Maier, Andreas (Journal of Quaternary Science, 2024)
We present sequential oxygen isotope records (δ18Ophosphate vs. VSMOW) of horse tooth enamel phosphate of six individuals from two adjacent Palaeolithic sites in Lower Austria. Three molars from the site Krems-Wachtberg date to 33–31k cal a bp, and three molars from Kammern-Grubgraben to 24–20k cal a bp. All teeth show seasonal isotope variations, which are used to reconstruct the annual oxygen isotope composition of drinking water (δ18Odw) and palaeotemperatures. Measured δ18Ophosphate values ranged from 8.6 to 13.0‰ and from 10.8 to 13.9‰ at Krems-Wachtberg and Kammern-Grubgraben, respectively. An inverse modelling approach was used to reconstruct summer and winter temperatures after a correction for glacial oceanic source water δ18O. Reconstructed annual δ18Odw was −16.4 ± 1.5‰ at Krems-Wachtberg and −15.3 ± 1.4‰ at Kammern-Grubgraben, resulting in annual temperatures of −5.7 ± 3.1 and −3.5 ± 2.9°C, respectively. Summer and winter temperatures reconstructed from individual teeth exhibit high seasonal variations with moderate summer temperatures and extremely low winter temperatures typical for a polar tundra climate. Isotopic differences between individuals are attributed to interannual climate variability or to different drinking water sources. Our reconstructed temperatures are, overall, consistent with previously reported values from European horse teeth, when taking regional differences into account. <br
Keywords: δ18O; last glacial maximum; palaeotemperatures; phosphate; seasonality; sequential sampling; Upper Palaeolithic

Stable isotope records of sei whale baleens from Chilean Patagonia as archives for feeding and migration behavior - Reiss, Lilian; Häussermann, Verena; Mayr, Christoph (Ecology and Evolution, 2019)
Carbon (δ13C) and nitrogen (δ15N) stable isotope variations in baleen plates of sei whales (Balaenoptera borealis) stranded after a mass mortality event in Chilean Patagonia were investigated to assess potential dietary and migratory patterns. Carbon and nitrogen isotope ratios of seven baleens from six individuals were analyzed. The δ13C values ranged from − 19.1 to − 15.9‰ and the δ15N values from 8.7 to 15.4‰. Variations of up to 2.9‰ for δ13C and 5.3‰ for δ15N were observed within one baleen. Carbon and nitrogen isotope records of each baleen were significantly correlated and showed recurring oscillations confirmed by wavelet analyses. Oscillations slightly differed in periodicity indicating variable baleen growth rates between 10.0 and 16.5 cm/year. Food sources of the whales are discussed in terms of available isotope data for potential prey taxa and potential migratory behavior on the basis of latitudinal isotope gradients of particulate organic matter. Cyclicity could be explained by regular migrations of the sei whales from subtropical calving areas to high-latitude foraging grounds. δ15N records of baleens differed between individuals eventually pointing to diverse feeding and migratory preferences among sei whale individuals.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Balaenoptera borealis; baleen growth rate; carbon isotopes; mass mortality event; nitrogen isotopes; Patagonian fjords